2022
DOI: 10.1007/s12542-022-00641-7
|View full text |Cite
|
Sign up to set email alerts
|

Turtle barnacles have been turtle riders for more than 30 million years

Abstract: In contrast to other kinds of biological interactions, symbiosis is a scarcely investigated aspect of the fossil record. This is largely due to taphonomic biases that often frustrate any attempt to make a strong case that two organisms shared an intimate association in life. Among extant marine vertebrates, the sea turtles (Cheloniidae and Dermochelyidae) bear a broad and diverse spectrum of epibiotic symbionts, including specialists such as the turtle barnacles (Chelonibiidae and Platyleapadidae). Here, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The fragmentary fossil record of turtle barnacles mostly comprises isolated shells and disarticulated wall plates. Occurrences of barnacle remains associated with those of the putative host organism(s) are exceedingly rare [25,[126][127][128]. Although morphofunctional considerations can provide some hints of what sort of host the extinct turtle barnacles might have been on [129][130][131], body fossils alone cannot disclose much information on the ancient basibionts of chelonibiids and platylepadids, nor on the nature of the intercurrent symbiotic association.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fragmentary fossil record of turtle barnacles mostly comprises isolated shells and disarticulated wall plates. Occurrences of barnacle remains associated with those of the putative host organism(s) are exceedingly rare [25,[126][127][128]. Although morphofunctional considerations can provide some hints of what sort of host the extinct turtle barnacles might have been on [129][130][131], body fossils alone cannot disclose much information on the ancient basibionts of chelonibiids and platylepadids, nor on the nature of the intercurrent symbiotic association.…”
Section: Discussionmentioning
confidence: 99%
“…They interpreted this scar, depicted in their figure 5E, as possibly caused by a sea turtle barnacle, which appears as reasonable (as well as consistent with the aforementioned divergence time estimates). Evidence that other lineages of turtle barnacles (i.e., archaic chelonibiids) inhabited the sea turtle shell as early as in early Oligocene times is provided by an exceptional cheloniid fossil, featuring Protochelonibia on its plastron-bottom, from the Rauenberg Fossil-Lagerstätte of southwestern Germany [25].…”
Section: Other Turtle Barnacle Scars In the Fossil Recordmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to overcome the limitations associated with a sessile lifestyle, some symbiont-bearing colonial corals have developed a simple solution: colonizing a "moving" substrate. The effectiveness of such an approach is evidenced by the many invertebrate lineages that have convergently adopted similar life habits: for instance, acorn barnacles of the superfamily Coronuloidea have become able to "ride" different motile substrates-whales, turtles, and crabs, to name just a few [15][16][17]. Choosing the right kind of living substrate can provide a sessile organism with most of the beneficial traits of a motile lifestyle, including the capability to escape unfavorable conditions, avoid predation, and survive burial.…”
Section: Of 13mentioning
confidence: 99%
“…The so called "turtle barnacles" indicate barnacle species that exclusively or preferentially live on carapace, plastron or skin of chelonians (Ross and Newman, 1967;Ross and Frick, 2011;Hayashi et al, 2013). It has been demonstrated that chelonibiids have been turtle-dwelling species for more than 30 million years (Collareta et al, 2023).…”
Section: Introductionmentioning
confidence: 99%